Design and Implementation of a Constant Tension Mid-Upper Arm Circumference (CT-MUAC) device for improved detection of malnutrition in children - Alam, Md Moiful; Haque, Rashida; Rabbani, K Siddique e (Bangladesh Journal of Medical Physics, 2019)
Mid-upper arm circumference (MUAC) is an important indicator of the nutritional index, particularly of children in low resource countries of the world. It is a significant anthropometric tool with simple cut-off values which is easy to implement in large scale screening measurements. A conventional MUAC device is essentially an insertion strap and has many merits over other anthropometric measurements techniques, but a lack of reproducibility in measurements is its leading problem since the measurement depends on how strongly a person pulls the strap around an arm of the subject. The aim of the present study is to minimize this reproducibility problem. For this the existing MUAC device has been modified using a short length of an elastic band to provide a constant tension while measuring, making it a Constant Tension MUAC device. Using both the MUAC devices (conventional and CT-MUAC), data were collected from seven subjects by 70 observers (10 observers measuring one subject). Statistical analyses showed that the CT-MUAC device gives a significant improvement with less variability over the conventional device. Thus, the new CT-MUAC device has the potential for improved detection of malnutrition throughout the world. Bangladesh Journal of Medical Physics Vol.11 No.1 2018 P 26-37